The practitioner's guide to child art therapy : fostering creativity and relational growth - Shore, Annette (New York : Routledge, 2013)
'For any clinician looking for guidance on the ins and outs of using art therapy with children, there is no better resource than The Practitioner's Guide to Child Art Therapy. Both graduate students and professionals will find its pages replete with strategies for developing engaging and effective strategies for understanding children's creative expression and applying this understanding toward treatment'--
Includes bibliographical references (pages 195-199) and index.
Keywords: Art therapy for children; Child psychotherapy; Art -- Study and teaching